2014
DOI: 10.1248/bpb.b13-00921
|View full text |Cite
|
Sign up to set email alerts
|

Danshensu Inhibits β-Adrenergic Receptors-Mediated Cardiac Fibrosis by ROS/p38 MAPK Axis

Abstract: Danshensu, the effective ingredient of the plant Salvia miltiorrhiza (Danshen), has been widely used for treatment of cardiovascular diseases. Cardiac fibrosis is an important process in pathological cardiac remodeling and leads to heart failure. We investigated the effect of Danshensu on β-adrenergic receptor (β-AR)-mediated cardiac fibrosis and the involved signaling transduction. Danshensu inhibited cardiofibroblast proliferation and collagen I synthesis induced by isoproterenol (ISO), a selective β-AR agon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 29 publications
2
45
0
Order By: Relevance
“…In this study, we found that ASA performed its anti-fibrotic function at least partly It has been reported that an increase in ROS levels is accompanied by p38 activation, fibrosis, apoptosis and cardiac dys- [18,30] . In this study, ASA inhibited levels of ROS and phosphorylated p38 when inhibiting fibrosis and apoptosis.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…In this study, we found that ASA performed its anti-fibrotic function at least partly It has been reported that an increase in ROS levels is accompanied by p38 activation, fibrosis, apoptosis and cardiac dys- [18,30] . In this study, ASA inhibited levels of ROS and phosphorylated p38 when inhibiting fibrosis and apoptosis.…”
Section: Discussionsupporting
confidence: 52%
“…The function of ROS in ASA-mediated inhibition of CF pro liferation and apoptosis Many ASA functions have been associated with inhibited ROS [17,18] . Here, our data showed that ASA inhibited ROS in CFs ( Figure 6A).…”
Section: Asa Alleviates Cf Proliferation By Inhibiting Autophagymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have confirmed that DSS has biological activities in that it improves microcirculation and exerts cardiovascular protective effects. For example, DSS has been shown to restore endothelium-dependent vasorelaxation via the prostacyclin pathway by increasing cyclooxygenase (COX)-2 gene expression and prostacyclin production (25), and thus it suppresses the formation of reactive oxygen species (ROS) and protects the myocardium against ischemia (26), protecting endothelial cells against injury induced by inflammation and inhibiting apoptosis (27,28), as well as inhibiting cardiac fibrosis through the negative regulation of ROS-/p38 MAPK signaling (29).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that DSS is an excellent candidate for removing blood stasis, improving microcirculation and preventing platelet from adhesion and aggregation (Lu et al 2014). In addition, single or repeated dose toxicity studies suggested that DSS does not cause any signs of toxicity ).…”
Section: Discussionmentioning
confidence: 99%